2013
DOI: 10.1186/1475-2867-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Functional features of cancer stem cells in melanoma cell lines

Abstract: BackgroundRecent evidence suggests a subset of cells within a tumor with "stem-like" characteristics. These cells are able to transplant tumors in immunodeficient hosts. Distinct from non-malignant stem cells, cancer stem cells (CSC) show low proliferative rates, high self-renewing capacity, propensity to differentiate into actively proliferating tumor cells, and resistance to chemotherapy or radiation. They are often characterized by elevated expression of stem cell surface markers, in particular CD133, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 31 publications
5
47
0
3
Order By: Relevance
“…Dormancy is another type of G 0 /G 1 arrest state and is often related to undifferentiated stem cells with downregulated metabolic process and protein translation (22)(23)(24)(25). CD133 is commonly used to identify SCLCCs in tumors, including melanomas (26,27). Here, we sorted CD133 hi tumor cells from B16 melanoma.…”
Section: Ifn-β Treatment Induces Stem Cell-like Melanoma Cells Into Dmentioning
confidence: 99%
“…Dormancy is another type of G 0 /G 1 arrest state and is often related to undifferentiated stem cells with downregulated metabolic process and protein translation (22)(23)(24)(25). CD133 is commonly used to identify SCLCCs in tumors, including melanomas (26,27). Here, we sorted CD133 hi tumor cells from B16 melanoma.…”
Section: Ifn-β Treatment Induces Stem Cell-like Melanoma Cells Into Dmentioning
confidence: 99%
“…The capacity of cancer cells to undergo EMT is now considered a hallmark of tumor metastasis (11,31). For this purpose, we tested EMT related molecular expression in the tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the knockdown of ZEB1 in B16F10 CD133 + CD44 + CSCs inhibited the tumorigenicity and distant lung metastasis potential. According to the CSC hypothesis, the tumorigenicity and metastasis potential represent mainly CSC-like properties in epithelial originated tumor cells (31,32). Consistent with the previously reported findings (2,5,6,17), our current study demonstrated that B16F10 CD133 + CD44 + CSCs had a multipotent, self-renewal capacity and strong tumorigenesis, while the decrease of ZEB1 expression in B16F10 CD133 + CD44 + CSCs caused reduction of CSC-like properties, which may be good evidence that ZEB1 serves as a crucial factor to maintain CSC-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 is currently identified as a cancer stem cell marker in various solid tumors, such as hepatocellular carcinoma (5), ovarian (6), colon (7) and esophageal carcinoma (8). Zimmerer et al (9) reported that as few as 500 CD133 + melanoma cells were able to form a tumor in NOD/SCID mice, whereas 100,000 CD133 -cells failed to do so; in addition, Taxol induced apoptosis in CD133 -cells, but not in CD133 + cells. These findings suggested that cancer stem cells have the ability to form the bulk of a tumor cell population and confer resistance to conventional therapy.…”
Section: Introductionmentioning
confidence: 99%